Fixed Export Costs and Export Behavior. (24th February 2016) - Castro, Luis; Li, Ben G.; Maskus, Keith E.; Xie, Yiqing
Abstract : This article provides a direct assessment of how fixed export costs (FECs) and productivity jointly determine firm‐level export behavior. Using Chilean data, we construct indices of FECs for each industry‐region‐year triplet and match them to domestic firms. Our empirical results show that firms facing higher estimated FECs are less likely to export, while those with higher productivity export more. These outcomes are the foundation of the widely‐used sorting mechanism in trade models with firm heterogeneity. We also find that the substitution between FECs and productivity in determining export decisions is weaker for firms with higher productivity. Finally, among firms that export, both larger FECs and greater within‐triplet productivity dispersion are associated with a greater export volume of the average exporter.